Hubungan Ibu Hamil sebagai Perokok Pasif dengan Berat Badan Lahir Rendah - Rika Setyowati; Sri Rahayu (Jurnal Sains & Kesehatan, 2022)
Smoking is a prohibited habit, both during pregnancy and not pregnant, both passive and active smoking. The negative impacts of cigarettes and their smoke on pregnant women and their fetuses include low birth weight (LBW) from normal (inhibited fetal growth) and this condition greatly affects the growth and development of the fetus. Abnormal body weight will easily cause growth and development obstacles. This study aims to determine the relationship between pregnant women as passive smokers with low birth weight at Syekh Yusuf Gowa Hospital. This research is a quantitative research with a case control approach which was carried out on March 17-April 17 2019 at Syekh Yusuf Gowa Hospital. The data obtained at Syekh Yusuf Gowa Hospital were 24 passive smokers and 6 non-passive smokers who experienced LBW incidents. Chi-square analysis found that 19 people (79.2%) experienced passive smokers with LBW events and 5 babies were born normal 20.8%) while non-passive smokers with LBW were 1 person (16.7%) and 5 people born normally (83.3%) obtained a value (ρ-value <0.5) with a value of ρ = 0.09 . The results showed that there was a relationship between passive smoking during pregnancy and low birth weight babies. The value of ρ = 0.009 is smaller than α = 0.05. From the results of the study, it is necessary to socialize in the community about the relationship between passive smoking during pregnancy and the incidence of LBW, so that pregnant women can find out the side effects due to exposure to cigarette smoke. In conclusion, there is a relationship between passive smoking during pregnancy and the incidence of LBW.